(untitled) (Educational Knowledge, 2017)
This article presents the results of a study conducted between 2015 and 2016 on the reliability of the Spanish Reading and Writing Test (LEE), an Argentine-Spanish battery, to analyze its applicability to Costa Rican students. The study employs an instrumental approach with a quantitative methodology, where reliability and internal consistency were determined using Cronbach’s alpha. The instrument was administered to a sample of 285 students from the Cartago educational region, the same area where the content validity of the same test was established in a study conducted between 2013 and 2014 (Carpio & Méndez, 2016). The overall results show that of this battery comprised of seven subtests, only the Word Reading, Pseudoword Reading, Word Writing, and Pseudoword Writing subtests can be used, with some modifications. For this reason, it is recommended that a specific test be developed for Costa Rica.